2021
DOI: 10.1016/j.animal.2021.100272
|View full text |Cite
|
Sign up to set email alerts
|

Review: SARS-CoV-2 infection in farmed minks – an overview of current knowledge on occurrence, disease and epidemiology

Abstract: Coronaviruses ( CoVs ), which are enveloped, positive-sense RNA viruses, may cause infections in mammals and birds. Apart from the respiratory manifestations, CoVs are also responsible for infections of the gastrointestinal tract and nervous systems. Their propensity to recombine allows them to easily transmit and adapt to new hosts. The emergence of a new CoV in humans, severe acute respiratory syndrome coronavirus 2 ( SARS-CoV-2 ), which is attributed to a zoonot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 51 publications
1
35
0
2
Order By: Relevance
“…Analysis of the genomic sequence suggested that these dogs were infected by their owners, who also tested positive for COVID-19 [ 14 ]. In addition natural SARS-CoV-2 infection has been reported in other domestic animal species such as cat, ferret and mink [ 13 , 37 ]. Although there is evidence of human-to-cat transmission [ 16 ], current data are not sufficient to definitively confirm the occurrence of SARS-CoV-2 in the domestic cat population as a result of cat-to-cat transmission, although high susceptibility of these animals has been found in experimental settings.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the genomic sequence suggested that these dogs were infected by their owners, who also tested positive for COVID-19 [ 14 ]. In addition natural SARS-CoV-2 infection has been reported in other domestic animal species such as cat, ferret and mink [ 13 , 37 ]. Although there is evidence of human-to-cat transmission [ 16 ], current data are not sufficient to definitively confirm the occurrence of SARS-CoV-2 in the domestic cat population as a result of cat-to-cat transmission, although high susceptibility of these animals has been found in experimental settings.…”
Section: Discussionmentioning
confidence: 99%
“…It is now increasingly apparent that SARS-CoV-2 has the capacity to infect several animal species besides humans, generating rising concerns that domestic and wild animals may become secondary reservoirs of the virus [5][6][7]. Outbreaks of COVID-19 in hundreds of mink farms in the EU [8], where identification of human-to-mink and mink-to-human virus transmissions [9,10] as well as mink-associated variants led to the culling of over 20 million minks in Denmark, underscored the importance of identifying and assessing the risks associated with the new pandemic for animal and human health [11][12][13][14]. Other animal species, including cats, dogs, ferrets, hamsters, non-human primates, white-tailed deer, mice, cattle, pigs, tree shrews, rabbits, raccoon dogs, and fruit bats, have also been investigated for their susceptibility to SARS-CoV-2 infection [15].…”
Section: Introductionmentioning
confidence: 99%
“…Bu durumu takiben, Mayıs 2020' de Avrupa'nın en büyük vizon kürkü üreticisi Danimarka' da ilk vakalar rapor edilmiştir (12). Bu çiftliklerde çalışan işçilerin % 68'inde virüsün pozitif olması veya SARS-CoV-2 antikorlarının saptanması ile Danimarka' da 4 Kasım 2020' de 13.000.000' dan fazla hayvan itlaf edilmiş ve vizon çiftlikleri kapatılmıştır (32,34). Daha sonra, İspanya, İsveç, İngiltere, ABD, Yunanistan, Fransa, Kanada, Litvanya ve Polonya' da da pek çok vaka rapor edilmiştir (26,31,32).…”
Section: Hayvanlar Açısından Covid-19 Pandemisi Süreciunclassified
“…Daha sonra, İspanya, İsveç, İngiltere, ABD, Yunanistan, Fransa, Kanada, Litvanya ve Polonya' da da pek çok vaka rapor edilmiştir (26,31,32). Ancak, antropo-zoonotik salgınlar sadece vizon çiftliklerinde belirlenmiş ve bu çiftliklerdeki hayvanların tamamı itlaf edilmiştir (34).…”
Section: Hayvanlar Açısından Covid-19 Pandemisi Süreciunclassified